2015
DOI: 10.1097/tp.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Prognosis in Elderly Solid Organ Transplant Recipients

Abstract: Background Treatment-related immunosuppression in organ transplant recipients has been linked to increased incidence and risk of progression for several malignancies. Using a population-based cancer cohort, we evaluated whether organ transplantation was associated with worse prognosis in elderly patients with non-small cell lung cancer (NSCLC). Methods Using the Surveillance, Epidemiology and End Results registry linked to Medicare claims we identified 597 patients age ≥65 with NSCLC who had received organ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
2
9
0
1
Order By: Relevance
“…71 Non-PTLD primary or metastatic lung cancer can also occur in SOT recipients. 72 Other complications such as pulmonary embolism, pulmonary hemorrhage, and pulmonary edema are also reported. 73,74…”
Section: Non-infectious Etiologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Non-PTLD primary or metastatic lung cancer can also occur in SOT recipients. 72 Other complications such as pulmonary embolism, pulmonary hemorrhage, and pulmonary edema are also reported. 73,74…”
Section: Non-infectious Etiologiesmentioning
confidence: 99%
“…16 Lung transplantation poses unique challenges given the potential for donor-derived infection and recipient airway colonization to impact the occurrence and microbiology of pneumonia. In a prospective, multicenter study of pneumonia in lung transplant recipients, pneumonia incidence was 72 and viral pneumonia together accounted for 24.4% of episodes. The majority of pneumonia episodes in this series occurred in the two months post-transplant.…”
Section: Considerations Impacting Differential Diagnosismentioning
confidence: 99%
“…Some studies have assessed prognosis among OTRs diagnosed with a few specific cancer forms . Compared to nontransplanted cancer patients, worse survival has been observed for OTRs diagnosed with colon cancer and melanoma whereas results have been mixed for nonsmall cell lung cancer . In light of these findings, it has been suggested that cancers developing in the context of transplant‐related immune suppression may have a different and more aggressive biology …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Compared to nontransplanted cancer patients, worse survival has been observed for OTRs diagnosed with colon cancer 12,14,15 and melanoma [17][18][19][20]24,26 whereas results have been mixed for nonsmall cell lung cancer. 14,22 In light of these findings, it has been suggested that cancers developing in the context of transplant-related immune suppression may have a different and more aggressive biology. 6,28 In this nationwide study, we aimed to assess if OTRs diagnosed with cancer have a worse survival compared to nontransplanted cancer patients across all major cancer types, accounting for type of transplanted organ, as well as cancer stage and histologic subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…A study in which researchers linked data from the Surveillance, Epidemiology and End Results Registry to Medicare claims identified patients with transplants and post-transplant cancers, including nonsmall cell lung cancer. The mean time from transplant to diagnosis of lung cancer was 3.3 years in the study (7). Although lung cancer is possible, given the timing of presentation and that the patient likely had CXRs around the time of transplantation that did not show these findings, lung cancer is less likely than pneumonia (choice A is incorrect).…”
Section: Discussion Of Question 1amentioning
confidence: 98%